Fraud on Taobao: an application of routine activity theory. (1st January 2013) - Fu, Paul; Nikitkov, Alexey N.; Bay, Darlene
This study investigates fraud on Taobao, an online auction house in China. We apply routine activity theory, which suggests that in order for a crime to occur three components must be present together: a motivated offender, a suitable target and the lack of a capable guardian. We survey 346 Taobao users and find strong support for the relationship of the crime rate with the presence of motivated offenders and the suitability of the target. We also find that, for the online environment, target suitability depends on factors that may be unique to this environment. Our results increase understanding of the fraud dynamic and provide information for effective choices for online information systems design, policies, and procedures. Further, we provide support for the applicability of routine activity theory in a virtual environment and in a non-Western marketplace.